Hepatitis C treatment initiation in HIV-HCV coinfected patients. Issue 1 (December 2016) - Cotte, Laurent; Pugliese, Pascal; Valantin, Marc-Antoine; Cuzin, Lise; Billaud, Eric; Duvivier, Claudine; Naqvi, Alissa; Cheret, Antoine; Rey, David; Pradat, Pierre; Poizot-Martin, Isabelle
Abstract Background There are few data regarding HCV treatment initiation among HIV/HCV coinfected patients. The objective of this study was to analyze the changing patterns of HCV coinfection and HCV treatment initiation over time in a large French cohort of HIV/HCV coinfected patients at the beginning of DAA's era and to analyze factors associated with treatment initiation. Methods All HIV/HCV coinfected patients enrolled during 2000–2012 were analyzed. HCV status was defined per calendar year as naïve, spontaneous cure, sustained virological response (SVR), failure or reinfection. HCV treatment initiation rate was determined per year. Trends over time were analyzed using Chi-2 test for trend and linear regression analysis. The effect of covariates on treatment initiation over time was analyzed using generalized estimating equations. Results Among 34, 308 HIV-infected patients enrolled between 2000 and 2012, 5, 562 were HCV coinfected. HCV prevalence declined from 38.4 to 15.1 %. HCV treatment initiation rate fluctuated from 5.6 to 7.4 %/year from 2000 to 2007, dropped to 5.6 % in 2011 and increased to 8.5 % in 2012 due to the use of first-generation DAAs (29.1 % of initiations in 2012). Cumulative HCV treatment initiation rate increased from 14.8 % in 2000 to 54.7 % in 2012. HCV cure rate increased from 12.4 to 45.2 %. Older age, male gender, male homosexuality, high CD4, undetectable HIV-RNA, CDC stage A-B, and severe fibrosis/cirrhosis were associated with a higher treatment initiation rate. The role of HCV genotype 1, CDC stage, fibrosis and recent HCV infection on treatment initiation rate changed over time. Conclusion A high rate of HCV treatment initiation was observed at the beginning of DAAs era in HIV/HCV coinfected patients. Given the very high efficacy of new DAA-based regimens and if treatment initiation keeps increasing, HCV prevalence among HIV patients will drastically decrease during the forthcoming years.